Cambridge companion to public law - Elliot, Mark,Ed (Cambridge companions to law, 2015)
"This collection of essays explores themes and controversies (legal, political and scholarly) in public law which are subjects of current debate in that area, while also (we hope) contributing to those debates from both practical and theoretical perspectives. The purposes of this Introduction are to set the scene by outlining the political context in which public law and its scholarship have developed over the past forty or so years, and to locate within that context and in relation to each other some of the themes which our contributors develop in the chapters which follow"--